Determinants of ESG Disclosure in ASEAN-5 Countries: A Legitimacy and Institutional Theory Approach - Kallisia, Maria Putri; Mukhibad, Hasan; Ali, Wanamina Bostan (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2025)
ESG disclosure among basic materials firms in the ASEAN-5 countries remains uneven, with notable implementation gaps. Drawing on legitimacy and institutional theories, this study employs moderated regression analysis on 185 firms from a population of 2.110 during 2019–2023 to identify key determinants of ESG reporting. Results reveal that carbon emission intensity and product disclosure. Results show that higher carbon emission intensity leads to greater ESG disclosure, suggesting firms seek legitimacy by providing extensive ESG information despite higher emissions. Firms with more diversified products also exhibit higher ESG disclosure, as complexity requires transparency to manage environmental and social risks. Contrary to expectations, business environmental uncertainty does not significantly influence ESG disclosure, supporting contingency theory’s view that no single strategy fits all firms in navigating uncertainty. Geographic location negatively affects ESG disclosure, highlighting resource constraints and underdeveloped ESG infrastructure, particularly in Indonesia. Gender diversity significantly moderates the effects of environmental uncertainty and geographic location, strengthening their impact on ESG disclosure. However, its interaction with carbon emission intensity and product diversification is not significant. These findings deepen understanding of the institutional and legitimacy factors influencing ESG disclosure in emerging markets.